The Basic Modern Principles and Approaches to Therapy of The Endogenous Psychoses with The First Attack at Youthful Age - Saparov Shingis Baxiyevich; Reymov Mukhamedali Kengesbayevich (Genius Publishing Group, 2021)
It was carried out detailed clinical and follow-up examination of 347 patients of youthful age (16–25 years), with the episodic type of schizophrenia (F20 in ICD-10), hospitalized with manifest psychotic attacks in clinic of MHRC of the RAMS during the period from 2000 to 2013.A number of the key provisions, allowing to structure approaches to the organization and carrying out therapeutic actions at patients with first attacks of the youthful schizophrenia was formulated. The main tactics of purpose of antipsychotic therapy at various stages of a course of schizophrenia was described, besides, need of use of methods of mental correction and social rehabilitation as a part of complex treatment of patients of youthful age was proved
Keywords: Schizophrenia; Youthful Age; Psychosis; Therapy